Pengaruh Ekonomi Makro terhadap Perubahan Laba Operasional Bank Umum Syariah di Bursa Efek Indonesia - Siti Nuraeni; Hj. St Nurhayati; Hamid, Abdul; Semaun, Syahriyah; Damirah (Institut Agama Islam Negeri Parepare, 2022)
This study endeavors to achieve the following objectives: (1) assess the extent of fluctuation in the operational profit of Islamic commercial banks, (2) investigate the impact of inflation on operational profit changes in Islamic commercial banks, (3) analyze the correlation between changes in national income and operational profit in Islamic commercial banks, (4) establish a significant and positive macroeconomic relationship with operational profit variations in Islamic commercial banks, (5) quantify the magnitude of macroeconomic influences on operational profit changes in Islamic commercial banks, and (6) explore potential simultaneous effects of inflation and national income on operational profit changes in Islamic commercial banks. The research employs a descriptive quantitative approach. The findings indicate a substantial and sharp decline in the operational profit of Islamic commercial banks during the period 2019-2021. While the partial analysis reveals no significant impact of inflation on operational profit changes in Islamic commercial banks, a similar lack of influence is observed between national income changes and operational profit fluctuations in Sharia commercial banks. Conversely, the study establishes a positive and statistically significant correlation between macroeconomic variables and operational profit changes in Islamic commercial banks. The Adjusted R Square value stands at 10%. Notably, a simultaneous analysis of inflation and national income variables suggests no combined effect on operational profit changes in Islamic commercial banks.